2021
DOI: 10.1136/bcr-2020-240687
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar aggressive angiomyxoma: a surgical challenge

Abstract: Aggressive angiomyxoma is a rare and locally aggressive mesenchymal tumour, predominantly occurring in women of reproductive age group. The term aggressive is attributed to the infiltrative nature and frequent local recurrences. They arise commonly from the vulvovaginal region, perineum or pelvis and are usually misdiagnosed as other common entities in these regions. Radiological investigations aid in the diagnosis and planning of surgery. However, the final diagnosis in most of the cases is established by his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Among the first-onset cases (65 cases), only seven patients were initially diagnosed with AAM, for which different auxiliary examinations were required. Three patients underwent needle biopsy ( 61 , 68 , 69 ), four MRI ( 51 , 60 , 61 , 68 ), and one ultrasound ( 53 ). For patients with incorrect initial diagnosis, bartholin's cyst or abscess and lipoma were the common conditions considered in the preliminary diagnosis .…”
Section: Resultsmentioning
confidence: 99%
“…Among the first-onset cases (65 cases), only seven patients were initially diagnosed with AAM, for which different auxiliary examinations were required. Three patients underwent needle biopsy ( 61 , 68 , 69 ), four MRI ( 51 , 60 , 61 , 68 ), and one ultrasound ( 53 ). For patients with incorrect initial diagnosis, bartholin's cyst or abscess and lipoma were the common conditions considered in the preliminary diagnosis .…”
Section: Resultsmentioning
confidence: 99%
“…This showed no statistically signi cant differences. In recent years, numerous studies have shown that incomplete or partial resection is acceptable, especially when high operative morbidity is anticipated and preservation of fertility is an issue (7,(18)(19)(20). The combination of incomplete resection with adjuvant therapy may be an effective treatment for AA, including hormonal therapy, arterial embolization, or radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Diana recommends that the evaluation of hormonal therapy as an adjunct to surgery is necessary (23). Other treatment modalities like angiographic embolization can be used in adjuvant setting and in cases where surgery is a contraindication or the possibility of obtaining a negative margin is dismal during resection (7). Furthermore, angiographic embolization as an alternative approach is not typically used solely and is often used in combination with other treatments, as the tumors usually being supplied with numerous feeding vessels (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations